Gastrointestinal helminths of commerson's dolphins Cephalorhynchus Commersonii from central Patagonia and Tierra del Fuego - Berón-Vera, Bábara (2001)
The stomachs and intestines of 9 Commerson's dolphins incidentally caught in trawl nets in central Patagonia and 23 stranded on beaches in Tierra del Fuego were surveyed for helminth parasites. A total of 267 individuals belonging to 4 species of parasites (1 nematode, 3 digeneans) were found in the dolphins from the first area: Anisakis sp. (larvae type 1 = A. simplex), Braunina cordiformis, Hadwenius sp. and Pholeter gastrophilus. In the Tierra del Fuego dolphins, 142 specimens belonging to 3 species (2 nematodes, 1 digenean, 1 cestode) were found: A. simplex, Hadwenius sp. and Strobilocephalus triangularis. Only 2 of the helminth species were shared in the 2 study areas, A. simplex and Hadwenius sp., and both were more common in central Patagonia. Among the species, A. simplex was most prevalent and abundant in both study areas. In Tierra del Fuego, adults of A. simplex appeared in only 1 host. Hadwenius sp., P. gastrophilus and S. triangularis are new host records for Commerson's dolphin. Species diversity and species richness were low in both study areas. Helminth communities were more diverse in central Patagonia (t = 1.97, df = 258, p < 0.05) and species richness was higher in central Patagonia (S = 4). No differences in diversity were observed between females and males of central Patagonia (t = 1.97, df = 139, p < 0.05) and between females of central Patagonia and Tierra del Fuego. The results may suggest some differences in habitat use, diet and sex between Commerson's dolphin populations in the 2 study areas.